Degenerate elliptic problem with a singular nonlinearity. Issue 5 (4th May 2023) - Sbai, Abdelaaziz; El hadfi, Youssef
ABSTRACT: In this paper, we prove existence and regularity results for solutions of some nonlinear Dirichlet problems for an elliptic equation defined by a degenerate coercive operator and a singular right-hand side (1) { − div ( a ( x, u, ∇ u ) ) = f u γ in Ω, u = 0 on ∂ Ω, where Ω is bounded open subset of I R N ( N ≥ 2 ), γ > 0 and f is a non-negative function that belongs to some Lebesgue space.